Copolímero Etileno Acetato de Vinila (EVA) como revestimento de papel cartão - Vilela, Thainá Moura (2025)
Growing environmental concerns are driving the search for sustainable packaging materials, with paper and cardboard standing out due to their recyclability. However, their limitations, such as low mechanical strength and moisture barrier, require functional coatings. Natural polymers, such as cationic starch and nanocellulose, have been studied as alternatives to synthetic ones, improving moisture resistance. The addition of mineral fillers, such as kaolin and calcium carbonate, affects opacity and water vapor barrier, while natural waxes, such as carnauba wax, increase hydrophobicity. Ethylene-vinyl acetate copolymers (EVA) are thermoplastics whose physicochemical properties, such as flexibility and impact resistance, make them competitive in the industry. This study analyzed the application of EVA as a coating for cardboard, evaluating thickness, grammage, wettability, tensile strength, and permeability to water vapor and oil. The polarity of EVA depends on the vinyl acetate content. When above 40%, it gives the material a more polar behavior, as evidenced by water and oil permeability analyses, where the paper presented excellent oil barrier properties. In addition, a high content also increases its viscosity, making uniform application difficult, as evidenced by scanning electron microscopy (SEM) analyses. The results indicate the potential of EVA as an adjuvant in packaging for sectors such as food, chemicals and cosmetics.